2017
DOI: 10.1002/ange.201703789
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐Doped BN Nanosheets for the Oxidative Dehydrogenation of Ethylbenzene

Fangsong Guo,
Pengju Yang,
Zhiming Pan
et al.

Abstract: Carbon-based catalysts have demonstrated great potential for the aerobic oxidative dehydrogenation reaction (ODH). However,its widespread application is retarded by the unavoidable deactivation owing to the appearance of coking or combustion under ODH conditions.T he synthesis and characterization of porous structure of BCN nanosheets as well as their application as anovel catalyst for ODH is reported. Such BCN nanosheets consist of hybridized, randomly distributed domains of h-BN and Cp hases,w here C, B, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 42 publications
3
31
0
1
Order By: Relevance
“…8 Recently, our group, followed by others reported that h-BN and BNNTs are surprisingly selective catalysts for the oxidative dehydrogenation (ODH) of alkanes to olefins. [9][10][11][12][13][14] For example, propane ODH at 500 °C over h-BN results in 76.0% selectivity to propylene, 11.5% to ethylene and only 9.4% to COx (CO plus CO2) at 19.1% propane conversion. These selectivities result in an olefin yields that are higher than obtained with state-of-theart supported vanadium oxide catalysts 15,16 while achieving good productivity (i.e., 2 kg propene per kg of catalyst per hour).…”
Section: Introductionmentioning
confidence: 99%
“…8 Recently, our group, followed by others reported that h-BN and BNNTs are surprisingly selective catalysts for the oxidative dehydrogenation (ODH) of alkanes to olefins. [9][10][11][12][13][14] For example, propane ODH at 500 °C over h-BN results in 76.0% selectivity to propylene, 11.5% to ethylene and only 9.4% to COx (CO plus CO2) at 19.1% propane conversion. These selectivities result in an olefin yields that are higher than obtained with state-of-theart supported vanadium oxide catalysts 15,16 while achieving good productivity (i.e., 2 kg propene per kg of catalyst per hour).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, hexagonal boron nitride (h-BN) and other boron-containing (bulk) materials have been reported as highly selective catalysts for the oxidative dehydrogenation (ODH) of light alkanes to olefins. [1][2][3][4][5][6][7][8] For all of these active materials, X-ray photoelectron spectroscopy (XPS) and InfraRed spectroscopy revealed the formation of oxidized boron species on the surface of the materials following catalytic testing for the ODH of propane. [7][8] We recently investigated spent h-BN ODH catalysts using (multidimensional) solid-state NMR spectroscopy, X-ray absorption spectroscopy (XAS), and scanning electron microscopy (SEM).…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of graphene domain also facilitates the electron transportation process, and BCN materials could impart carbon catalysis to BN materials for several catalytic applications with notable activity enhancement (16,17). For example, BCN nanosheets exhibit both high activity and excellent oxidation resistance in ODH of ethylbenzene to styrene (18), as well as notable catalytic activity for oxygen reduction (19). However, the catalytic applications of BCN materials are still at an early proof of concept stage (20), and the molecular design and synthesis of BCN catalysts and quantification of the catalytic activity of each functionality remain to be explored (21).…”
Section: Introductionmentioning
confidence: 99%